Microbiome Innovation in Agriculture: Development of Microbial Based Tools for Insect Pest Management - Qadri, Masroor; Short, Sierra; Gast, Kalani; Hernandez, Jordan; Wong, Adam Chun-Nin (Frontiers in Sustainable Food Systems, 2020)
This review emphasizes the potential and use of microbes in sustainable insect pest management. We first review the diverse insect traits shaped by insect-microbe associations that span nutrition, immunity, ecological interactions with natural enemy, insecticide resistance, and behavior. This is followed by discussing different microbiome manipulation approaches to alter pest traits, describing some of the opportunities and obstacles for each approach. We then highlight microbiomes as untapped chemical inventories to discover novel biopesticides, including plant-incorporated protectants and semiochemicals. The last topic covered is the use of beneficial microbes to improve mass-reared insects' performance for autocidal programs, including sterile insect technique and incompatible insect technique, in which we identify topics where data are limited or inconclusive, for future research.